Investigating Vascular Complexity and Neurogenic Alterations in Sectoral Regions of the Retina in Patients With Cognitive Impairment - Cabrera DeBuc, Delia; Feuer, William J.; Persad, Patrice J.; Somfai, Gabor Mark; Kostic, Maja; Oropesa, Susel; Mendoza Santiesteban, Carlos (Frontiers in Physiology, 2020)
Evidence is accumulating that cognitive function, and visual impairment may be related. In this pilot study, we investigated whether multifractal dimension and lacunarity analyses performed in sectoral regions of the retina may reveal changes in patients with cognitive impairment (CI) that may be masked in the study considering the whole retinal branching pattern. Prospective age-matched subjects (n=69) with and with no CI and without the presence of any ophthalmic history were recruited (age>55+ years). The Montreal Cognitive Assessment was used to measure cognitive impairment, and full-field electroretinogram (ERG) was performed. Also, visual performance exams were conducted using the Rabin cone contrast test (CCT). Quantification of the retinal structure was performed in retinal fundus images (45o FOV, optic disc centered) with excellent quality for all individuals (19 healthy controls (HC) and 20 patients with CI) after evaluating the inclusion and exclusion criteria in all study participants recruited (n=69). The skeletonized vasculature network that comprised the whole branching pattern observable in the full 45° FOV was obtained for each image and divided into nine equal regions (superotemporal, superior, superonasal, macular, optic disc, nasal, inferotemporal, inferior, inferonasal). The multifractal behavior was analyzed by calculating the generalized dimension Dq (Do, D1, D2), the lacunarity parameter (Λ) and singularity spectrum f(α) in the nine sectoral skeletonized images as well as in the skeletons that comprised the whole branching pattern observable in the full 45° FOV. The analyses were performed using the ImageJ program together with the FracLac plug-in. Independent sample t-tests or Mann Whitney U test and Pearson correlation coefficient were used to finding associations between all parameters in both groups. The effect size (Cohen’s d) of the difference between both groups was also assessed. A p-value < 0.05 was considered statistically significant. Significant correlations between multifractal and lacunarity parameters with the MoCA and implicit time ERG-parameter were observed in the regional analysis. In contrast, no trend was found when considering the whole retinal branching pattern. Analysis of combined structural-functional parameters in sectoral regions of the retina, instead of individual retinal biomarkers, may provide a useful clinical marker of CI.